Integrated metagenomics and transcriptomics analysis reveals pathways associated with oral periapical lesions formation and progression - Alaa Muayad Altaie; Thenmozhi Venkatachalam; Kiran Patil; Farah Al-Marzooq; Surendra Singh Rawat; Ali Al Qabbani; Mohammed Amjed Alsaegh; Lakshman P. Samaranayake; Sameh S.M. Soliman; Rifat Hamoudi (Current Research in Microbial Sciences)
Periapical abscesses, radicular cysts, and periapical granulomas are among the most frequently identified pathological lesions in the alveolar bone. Although many studies have investigated bacterial metagenomics in periapical abscesses, little is known about the genome mining of abundant bacteria in periapical lesions and its correlation to human transcriptome. This study aims to explore the enriched metabolic environment of periapical lesions associated with microbial diversity and their role in lesion progression. Bacterial DNA and human RNA were isolated from periapical lesions and healthy pulp tissue and sequenced using next-generation sequencing (NGS). The sequences of the most abundant bacteria were then analyzed to identify secondary metabolites, pathogenic proteins, and their associated metabolic pathways. The results revealed that Fusobacterium nucleatum was the predominant bacterium in periapical abscesses and radicular cysts, whereas Porphyromonas endodontalis was the most abundant in periapical granulomas. Integrated bacterial and human metabolic pathways indicated that the augmentation of similar pathways is important in lesions pathogenesis. In periapical abscesses, inflammatory response, humoral immune response, positive regulation of cell migration, and hemopoiesis were enriched. In radicular cysts, pathways linked to NABA matrisome associated, inflammatory response, immune response-regulating signaling pathway, neutrophil degranulation, and P73 pathway were enriched. Meanwhile, periapical granulomas exhibited significant enrichment of pathways related to response to bacterium, regulation of immune effector process, and positive regulation of cell migration. In conclusion, this study is the first to elucidate the interplay between microbial and human metabolic activity associated with inflammation in abscesses, apoptosis in cysts, and inflammatory regulation in granulomas. These findings have significant clinical implications for the early diagnosis, prevention, and treatment of periapical lesions.